The unconstitutionality of Article 6 in the Law of Public Sector Budget for 2014 and the Fiftieth Eighth Complementary and Final Provision of the Law of Public Sector Budget for 2013 - Prado Huayanay, Rubí (2014)
Collective bargaining is the main tool for harmonizing conflicts of interests in a working relationship. Restrictions to this right have become important in the Public Sector due to their intensive process when establishing. Prohibition of wage increases through collective bargaining has led the government work in the last 9 years. The Budget Laws for 2013 and 2014 have adopted provisions that endure this restriction. The following paper pretends to analyze these restrictions validity from the parameters given by the Constitution and the International Agreements on the matter.